2001
DOI: 10.1139/x01-017
|View full text |Cite
|
Sign up to set email alerts
|

Whole-tree biomass and carbon allocation of juvenile trees of loblolly pine (Pinustaeda): influence of genetics and fertilization

Abstract: To assess the contribution of belowground biomass allocation towards total carbon (C) allocation of two provenances of loblolly pine (Pinus taeda L.), we examined the total biomass allocation of a fast- and slow-growing family from each provenance. Since planting on a xeric, infertile site in Scotland County, N.C., U.S.A., trees in this study have been subjected to one of two nutrient treatments: optimal nutrition or control (no fertilization). Total biomass of 24 (1 tree/family plot × 2 families × 2 provenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 23 publications
(12 reference statements)
5
44
1
Order By: Relevance
“…In addition, their greater ages made it more likely that they experienced crown damage from weather events (e.g., ice or wind storms) that periodically affect the study area, although saplings with obvious impacts were excluded from sampling. Similar to other studies (e.g., Retzlaff et al 2001), our data found loblolly pine taproots to contribute approximately 15% of the total biomass. The effects of stem origin on taproot biomass emerged for stems greater than 8 cm dbh (Figure 3).…”
Section: Discussion Local Biomass Model Outcomessupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, their greater ages made it more likely that they experienced crown damage from weather events (e.g., ice or wind storms) that periodically affect the study area, although saplings with obvious impacts were excluded from sampling. Similar to other studies (e.g., Retzlaff et al 2001), our data found loblolly pine taproots to contribute approximately 15% of the total biomass. The effects of stem origin on taproot biomass emerged for stems greater than 8 cm dbh (Figure 3).…”
Section: Discussion Local Biomass Model Outcomessupporting
confidence: 91%
“…The additional biomass in taproots of natural-origin stems may have implications for carbon storage. Taproots, which represent the largest root fraction (Retzlaff et al 2001), are slow to decay Kapeluck 1995, Ludovici et al 2002). Increasing management of natural forests to decrease rotation lengths will increase carbon stocks sequestered in taproot biomass .…”
Section: Discussion Local Biomass Model Outcomesmentioning
confidence: 99%
“…Contrast comparisons showed that fertilization significantly increased diameter, height, and volume after year one, but only height and volume after year two (Table 2). These results are in agreement with other studies examining the effects of fertilization on P. faeda growth in the Southeast (Samuelson 1998, Jokela and Martin 2000, Retzlaff et al 2001, Yin and Sedjo 2001. Irrigation and fertilization, in addition to weed control, significantly increased tree height and volume after each of the first three growing seasons in the Georgia Coastal Plain (Nowak and Berisford 2000).…”
Section: Resultssupporting
confidence: 93%
“…Particularly susceptible is loblolly pine, Pinus faeda L., the most commercially important tree species in the southeastern U.S. (Schultz Intensively-managed forest plantations now occupy over 14 million ha of timberland in the southeastern U.S. (Guldin and Wigley 1998). Large gains in P. faeda productivity can be achieved with intensive forest management practices such as herbaceous weed control, irrigation and fertilization (Pritchett and Smith 1972, Jokela and Martin 2000, Nowak and Berisford 2000, Borders and Bailey 2001, Retzlaff et al 2001. However, intensive management has, at times, resulted in an increased frequency and severity of pest infestations (Cade andHedden 1987, Ross et al 1990).…”
mentioning
confidence: 99%
“…The ratio of belowground to aboveground biomass is one commonly studied allometric relationship. Most studies have found the root-shoot ratio in loblolly is highly ontogenetic, especially for long-term data on different resource gradients [24][25][26]. Coyle, et al [25] has provided a composite of the literature concerning loblolly root-shoot allometry.…”
Section: Introductionmentioning
confidence: 99%